EFFECT OF DEMOCRATIC LEADERSHIP STYLE ON THE PERFORMANCE OF EMPLOYEES AT THE OFFICE BP3K LANDONO DISTRICT OF SOUTH KONAWE - Aprianto Rahman; Helviani Helviani (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2016)
This study aims to determine how the democratic leadership style influence an office manager to employee performance at the Office BP3K Landono district of South Konawe. The location determination is based on the consideration that because researchers have been doing field practice course at the site on the planning and evaluation of agricultural programs that relate how the leadership of these locations in the lead so that these activities can run smoothly. So the researcher interested in conducting further research on leadership style that is applied in particular to the leadership of a democratic leadership style. Analysis of the data used is descriptive qualitative by using a model of Miles and Huberman. A democratic leadership style office management affects employee performance, including quality, quantity, timeliness, independence, and commitment to work in the Office of the District BP3K Landono Konsel. Leaders should approach issues with an open mind along with employees, for example by holding a meeting (conference) or deliberations to discuss the matter in order to reach a decision together and we always seek to establish good cooperation relationship with subordinates, receive inputs in determining policy, and work actively with individuals or groups to do the job.